Effectiveness of the US Centers for Disease Control and Prevention HEADS UP coaches’ online training as an educational intervention - Daugherty, Jill (Health Educ J, 2019)
BACKGROUND: Concussions are common among youth athletes. Responsibility for the recognition and management of concussion is often put on coaches. To equip coaches with appropriate knowledge and skills, the US Centers for Disease Control and Prevention (CDC) launched the HEADS UP: Concussion in Youth Sports online training. OBJECTIVES: To determine whether HEADS UP coaches’ training improves knowledge, attitudes and behavioural intentions. METHODS: Knowledge questions were grouped into scales by level of difficulty. Differences between pre-and post-test scores were calculated based on the Wilcoxon Signed Rank Test Z-score and effect sizes were interpreted. RESULTS: Coaches displayed a high level of knowledge in the pre-test. While lower difficulty questions did not show improvement from pre- to post-test, moderate and high difficulty questions did. Use of the training was associated with improved knowledge about symptom resolution, return-to-play recommendations and under-reporting of incidents of concussion. Coaches demonstrated improvement in five of the seven concussion-related attitude and behavioural intention items post training. CONCLUSION: HEADS UP training improved coaches’ knowledge on select topics and helped them feel more comfortable about responding to concussion among their athletes. This study provides insight into how to better focus future HEADS UP concussion health education efforts to fit coaches’ informational needs.